IMPLEMENTASI PEMBELAJARAN TARI JEPIN LANGKAH SIMPANG PADA SISWA KELAS XF SMA NEGERI 10 PONTIANAK - Ismunandar, Ismunandar; Wartiningsih, Agus; Billah, Mu’tashim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe study implementation of Jepin Langkah Simpang dance with drill method to improve students skills in class X SMA Negeri 10 Pontianak. Researcher used descriptive method in this study. The result of the analysis about study implementation of Jepin Langkah Simpang dance with drill method is that using drill method can enhance students skills and can make students better than of learning process in from skills, especially in the field of dance. Techniques of data collection are observation, interview, documention, and performance test. The technique of data validaty testing triangulation technique. Data analysis technique in this research are analyzed and interpret actifity, actifity process, result of actifity, doing a discussion with supervisor and conclude the result of analysis about study implementation of Jepin Langkah Simpang dance with drill method to improve students skills in class X SMA Negeri 10 Pontianak.The result of this research are expected to be implemented in a cultural art lesson on Senior High School X grade first semester and it can be refrences for further analysis about implementation learning.Keywords: drill method, implementation, Jepin Langkah Simpang dance, study